Dityrosine cross-linking and its potential roles in Alzheimer’s disease - Maina, Mahmoud B.; Al-Hilaly, Youssra K.; Serpell, Louise C. (Frontiers in Neuroscience, 2023)
Oxidative stress is a significant source of damage that accumulates during aging and contributes to Alzheimer’s disease (AD) pathogenesis. Oxidation of proteins can give rise to covalent links between adjacent tyrosines known as dityrosine (DiY) cross-linking, amongst other modifications, and this observation suggests that DiY could serve as a biomarker of accumulated oxidative stress over the lifespan. Many studies have focused on understanding the contribution of DiY to AD pathogenesis and have revealed that DiY crosslinks can be found in both Aβ and tau deposits – the two key proteins involved in the formation of amyloid plaques and tau tangles, respectively. However, there is no consensus yet in the field on the impact of DiY on Aβ and tau function, aggregation, and toxicity. Here we review the current understanding of the role of DiY on Aβ and tau gathered over the last 20 years since the first observation, and discuss the effect of this modification for Aβ and tau aggregation, and its potential as a biomarker for AD.